Metode Nucleic Acid Test untuk Uji Saring Virus Hepatitis B pada Darah Donor dengan Hepatitis B Occult - Suryani, Ulfah; Setiawaty, Vivi (Jurnal Biotek Medisiana Indonesia, 2015)
HBsAg is the primary screening at the Blood Transfusion Unit (UTD) in Indonesia. Blood with HBsAg negative still have potential to transmit the Hepatitis B Virus (HBV) infection. To improve blood safety, examination needs to be done is the detection of HBV DNA in window period. This study aim to determine the NAT can detect HBV DNA positive in blood donors with Occult Hepatitis B (HBO). A cross-sectional study on 4973 blood samples from the donor 4 UTD: DKI Jakarta, Tangerang district and municipality, Depok. Examination of HBsAg, anti - HBc, anti - HBs done UTD while NAT, quantitative and qualitative PCR, performed at the Eijkman Institute for Molecular Biology . Quantitative and qualitative PCR performed to measure viral load that is used as a confirmation of HBV were detected by the method of NAT. A 20 of 4973 subjects (0.4%) had negative results and NAT multiplex HBsAg positive. 16 of the 20 subjects of HBsAg negative and positive discriminatory NAT. Results of the examination of anti-HBc anti-HBs negative and positive / negative feedback only one subject (6.25%), 9 samples positive anti-HBc and anti-HBs negative (56.25%), the results of anti-HBc and anti- HBs positive 5 samples (31.25%). The results of qualitative and quantitative PCR obtained three samples (18.75%) are not detectable, 6 (37.5%) samples showed results of a high viral load and 7 samples (43.75%) showed low detection. The NAT assay which was performed as a screening of donor blood parameters are effective to detect HBV DNA in blood donors with HBO.Key words. Hepatitis B occult, Nucleic Acid Test, Blood DonorAbstrakHBsAg merupakan pemeriksaan utama di Unit Transfusi Darah (UTD) di Indonesia. Darah HBsAg negatif masih berpotensi menularkan infeksi Virus Hepatitis B (VHB). Untuk meningkatkan keamanan darah, perlu dilakukan pemeriksaan yang dapat mendeteksi DNA VHB pada window period. Penelitian ini bertujuan untuk mengetahui pemeriksaan Nucleic Acid Test (NAT) dalam mendeteksi DNA VHB pada darah donor dengan Hepatitis B Occult (HBO). Penelitian potong lintang terhadap 4973 sampel darah donor dari 4 UTD, yaitu DKI Jakarta, kota dan kabupaten Tangerang, kota Depok. Pemeriksaan HBsAg, anti-HBc, anti-HBs dilakukan UTD sedangkan NAT, PCR kuantitatif dan kualitatif, dilakukan di Lembaga Biologi Molekuler Eijkman. Pemeriksaan PCR kuantitatif dan kualitatif dilakukan untuk menghitung viral load yang digunakan sebagai konfirmasi VHB yang berhasil dideteksi dengan metode NAT. Sebanyak 20 dari 4973 subjek (0,4%) mempunyai hasil HBsAg negatif dan NAT multipleks positif. 16 dari 20 subyek HBsAg negatif dan NAT discriminatory positif. Hasil pemeriksaan anti-HBc negatif dan anti-HBs positif/negatif didapatkan hanya satu subyek (6,25%), 9 sampel anti-HBc positif dan anti-HBs negatif (56,25%), hasil pemeriksaan anti-HBc dan anti-HBs positif 5 sampel (31,25%). Hasil pemeriksaan PCR kualitatif dan kuantitatif didapatkan 3 sampel (18,75%) tidak terdeteksi, 6 (37,5%) sampel menunjukkan hasil viral load yang tinggi dan 7 sampel (43,75%)menunjukkan low detection. Pemeriksaan NAT sebagai parameter uji saring darah donor efektif untuk mendeteksi DNA VHB pada darah donor dengan HBO.Kata kunci: Hepatitis B Occult, Nucleic Acid Test, Donor Darah